2020
DOI: 10.3390/cells9030720
|View full text |Cite
|
Sign up to set email alerts
|

An Overview on ERAP Roles in Infectious Diseases

Abstract: Endoplasmic reticulum (ER) aminopeptidases ERAP1 and ERAP2 (ERAPs) are crucial enzymes shaping the major histocompatibility complex I (MHC I) immunopeptidome. In the ER, these enzymes cooperate in trimming the N-terminal residues from precursors peptides, so as to generate optimal-length antigens to fit into the MHC class I groove. Alteration or loss of ERAPs function significantly modify the repertoire of antigens presented by MHC I molecules, severely affecting the activation of both NK and CD8 + T cells. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 122 publications
1
42
0
2
Order By: Relevance
“…The involvement of ERAPs in modulating viral infections is widely recognized as recently reviewed in [ 34 ]. Several studies, indeed, have demonstrated the intervention of ERAP genetic variants in the life cycle of HCV, flu, CMV, HPV, HIV, and other pathogens at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of ERAPs in modulating viral infections is widely recognized as recently reviewed in [ 34 ]. Several studies, indeed, have demonstrated the intervention of ERAP genetic variants in the life cycle of HCV, flu, CMV, HPV, HIV, and other pathogens at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…The role of ERAP1 in modulating susceptibility to infections from HCV, HCMV, influenza virus, HPV, HIV, and toxoplasma has been exhaustively reviewed by Saulle et al [59] and Yao et al [60]. Several ERAP1 variants affecting disease susceptibility and/or progression have been identified.…”
Section: Functional Consequences Of Erap1 Polymorphisms In Human Disementioning
confidence: 99%
“…They were located both in coding (rs30187, rs27044, rs26618, rs10050860, rs26618, rs26653, rs17481856) and non-coding regions, including intronic (rs149481, rs27042, rs149173, rs17481856) and 3 UTR (rs17481334) regions. Genetic variants in the ERAP1 coding region-rs27044, rs26653, rs10050860, rs26618, rs26653, rs17481856, and rs30187-have been associated with susceptibility to HIV, HCV, HPV, and/or toxoplasmosis infection [59,60]. The intronic variants rs149481, rs27042, rs149173, and rs17481856 have been associated with susceptibility to Toxoplasma gondii infection, Kawasaki disease, chronic hepatitis C, and HIV [59,60].…”
Section: Functional Consequences Of Erap1 Polymorphisms In Human Disementioning
confidence: 99%
See 2 more Smart Citations